2021
DOI: 10.1109/jstars.2021.3110896
|View full text |Cite
|
Sign up to set email alerts
|

Geoparcel-Based Spatial Prediction Method for Grassland Fractional Vegetation Cover Mapping

Abstract: Grassland resources guarantee the balance of ecosystems and the sustainable development of animal husbandry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Through field investigations and Region of Interest (ROI) analysis in ENVI, it was found that the spectral curves of A. frigida communities in desert grasslands become flat and featureless due to drought stress. This change makes it difficult to distinguish pixels that are mixed with S. breviflora in the image, leading to issues such as same-spectrum foreign bodies and homogeneous spectra [ 23 , 24 ]. This is also a challenging task in the current research on desert grassland land cover classification and inversion and has become a key technical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Through field investigations and Region of Interest (ROI) analysis in ENVI, it was found that the spectral curves of A. frigida communities in desert grasslands become flat and featureless due to drought stress. This change makes it difficult to distinguish pixels that are mixed with S. breviflora in the image, leading to issues such as same-spectrum foreign bodies and homogeneous spectra [ 23 , 24 ]. This is also a challenging task in the current research on desert grassland land cover classification and inversion and has become a key technical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Unique prediction alone is not enough to map the vegetation accurately. Fractional vegetation mapping is required to estimate the regular coverage in the spatial resolution method [6]. Considering the surface analysis framework in urban areas, the intensity variations and heat are monitored despite temperature changes in various zones.…”
Section: Introductionmentioning
confidence: 99%
“…Kriging also has certain expansion, such as Universal Kriging(UK) (Xuan Thanh et al, 2015), Kriging with External Drift(KED) (Berndt et al, 2014). Wu et al (2021) uses geographical map spot as basic mapping units. In comparison with traditional regular grid-based methods, it achieves higher accuracy.…”
Section: Introductionmentioning
confidence: 99%